Modeling of the Oxidation of Lignite and Calculation of Carbon Footprint in the Gas Phase - Maimekov, Timur; Sambaeva, Damira; Maimekov, Zarlyk; Zheenbaev, Nurbek; Kemelov, Kubat; Moldobaev, Mirlan (International Journal of Environmental Science and Green Technology, ISSN: 3080-8693, 2025)
The paper examines local coal sources and presents their physicochemical characteristics. The Kara-Keche coal deposit has been adopted as the model system, with the following composition percentages: hydrogen (H) - 3.65%, carbon (C) - 79.03%, nitrogen (N) - 0.84%, sulfur (S) - 0.55%, and moisture content considering oxygen (H2O) - 18.47%. Thermodynamic modeling of the coal oxidation process at the maximum entropy of the system was carried out. The concentration distribution of components containing H, C, N, S, and O, as well as active particles and condensed phases, was established over a wide temperature range (298-3000 K). At the theoretical combustion temperature of coal (1998 K), the complete composition of carbon-containing substances in the gas phase was determined, and the additive value of the carbon footprint was calculated for the first time, taking into account the initial mass of carbon in the solid phase. The anthropogenic carbon load in the gas phase is useful for assessing the carbon capacity per unit of industrial production obtained from the combustion of solid fuel.